Conserving threatened plants of Bangladesh: Miles to go before we start? - Irfanullah, Haseeb Md (Bangladesh Journal of Plant Taxonomy, 2011)
In the light of important developments in biodiversity conservation in the global and national arenas over the last decade (2001-2010), this paper appraises the progress in identifying threatened vascular plant species of Bangladesh as a primary step of species diversity conservation. It is argued that, as per the IUCN Red List categories and the Volume 1 of ‘Red Data Book of Vascular Plants of Bangladesh’ published in 2001, only four angiosperm species are threatened (1 Critically Endangered (CR), 1 Endangered (EN), 2 Vulnerable (VU)) in Bangladesh, not 106 vascular species. This account also records that, accordingly to the ‘Encyclopedia of Flora and Fauna of Bangladesh’ (2007-2009; Volumes 5-12), 36 pteridophyte species (all VU; 18.46% of 195 recorded species), 1 gymnosperm species (EN; 14.29% of 7 species), and 449 angiosperm species (30 CR, 126 EN, 293 VU; 12.43% of 3,611 recorded species) are threatened in the country. The paper discusses and explores the importance, limitations and opportunities for red listing of threatened plants of Bangladesh. This account further advocates for a well-planned initiative to effectively complete the Red List of threatened plant species of the country by considering appropriate, established, updated assessment methods; following collaborative approach; and capitalizing on the progress made so far. Such steps may subsequently contribute to the species diversity conservation endeavours in Bangladesh. Keywords: Angiosperm; Biodiversity; Convention on Biological Diversity; Red Data Book; Red List; Vascular plants. DOI: 10.3329/bjpt.v18i1.7844 Bangladesh J. Plant Taxon. 18(1): 81-91, 2011 (June)